Weathering challenges: Distributional impacts of climatic shocks on household consumption in Mozambique - Patricia Justino; Gabriel Facundes Monteiro; Rodrigo Carvalho Oliveira; Edson R. Severnini (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2025)
Mozambique is highly vulnerable to climate change. It faces frequent cyclones, floods, and droughts while having limited revenue collection capacity and social protection programmes. This paper assesses the distributional effects of climate shocks on household consumption and explores adaptation strategies using consumption survey data from 2008 to 2022, combined with district-level climate data. We find that extreme rainfall and dryness shocks during the growing season significantly reduce household expenses for essential goods, with impacts most pronounced at the bottom to the middle of the consumption distribution. However, we found that the consumption of self-produced goods mitigates the expense losses. Our findings suggest that the main social protection programme in the country, PSSB, also helps mitigate these negative effects. We do not find evidence that domestic family transfer and international remittances cushion consumption losses because of climate shocks. This study underscores the importance of developing targeted policies to protect households in vulnerable regions as climate risks intensify.
Keywords: Q54; I30; Q56; 330; Mozambique; consumption; inequality; climate shocks; poverty